A Review of the Impact of Livestock Interventions on Food and Nutrition Security and Adaptive Capacity of Farm Households and Greenhouse Gas Emissions in Ethiopia - Mekuriaw, Shigdaf; van Dijk, Suzanne; Taye, Mengistie; Megersa, Bekele; Nigatu, Shimelis; Sheferaw, Desie; Chalchisa, Tamiru; Haile, Aynalem; Sori, Teshale; Najir, Dina; Wassie. Shimels; Wilkes, Andreas; et al. (International Livestock Research Institute, 2025)
Ethiopia has the largest livestock population in Africa. The livestock production system is predominantly extensive, with indigenous breeds and low-input husbandry practices. The sector's productivity is constrained by several factors, including low productivity, poor quality and varying seasonal availability of feed, high disease incidence and parasite challenges, and limited access to animal health services and inputs. Different livestock interventions have been implemented to respond to these production challenges and improve livestock productivity. This review aims to synthesize the impact of livestock interventions on food and nutrition security (FNS), adaptive capacity and gender empowerment of farm households and greenhouse gas (GHG) emissions in Ethiopia. A comprehensive literature review using appropriate keywords was implemented using Google Scholar, PubMed and African Journals online. Eligible studies were selected based on predefined inclusion and exclusion criteria. Accordingly, one hundred thirty-three (133) original research papers published from data collected in various parts of Ethiopia were included. A standardized form was used to extract data from the included studies. The extracted data was summarized and synthesized, and key outcomes were presented with narratives, tables and figures. Among the livestock interventions implemented in the past in Ethiopia, Community-Based Breeding Programs (CBBP) have been a significant practice in Ethiopia, and a wide range of reports have raised the improvement in animal performance and genetic gain. CBBP has improved household income from the sale of animals, improving dietary diversity at the household level and impacting individual nutritional outcomes. The integration of small ruminant interventions such as CBBP, animal health, feed and forage, and marketing strategies positively impacted the transformation of the sector and the livelihoods of society. The review findings show that CBBP has improved household mutton consumption, increasing productivity and income from sheep production. The ongoing CBBP tailored the involvement of women through training and the establishment of women-led CBBPs. Since 2019, seven women-led CBBPs with 486 members have been established. Interventions implemented in conjunction with CBBP, such as animal health, improved feed, and selection for fast-growing animals, have a synergy and trade-off in lowering the environmental footprint under the extensive production system in Ethiopia. Moreover, animal health interventions such as vaccinations and de-worming contribute to food security and nutrition outcomes. Furthermore, it needs to align these livestock interventions with climate-smart livestock production targeted to lowering the climate burden of greenhouse gases, and increased sustainability is mandatory. In conclusion, though sufficient success was recorded with CBBP, the program is still challenged by technical, financial, and institutional factors at different levels. However, there is limited evidence on the impact of CBBP and animal health interventions on food nutrition security, adaptive capacity, greenhouse gas emissions, gender and political economy in Ethiopia.